Effect of multi-layered nanosheets γ-Al2O3 with (110) facets on zinc deactivation resistance for Ce–Ti SCR catalyst. (April 2022) - Gong, Pijun; He, Feng; Xie, Junlin; Wu, Haitao
Abstract: Zn species that exist in the flue gas are dangerous toxicants for SCR catalysts, which will seriously damage its catalytic activity and service life. Hence, the multi-layered nanosheets γ-Al2 O3 with (110) facets were introduced into the CeTiOx catalyst to improve the Zn-poisoning resistance performance. Benefiting from the structural and compositional merits, as well as the superior reducibility, abundant acid sites, and chemisorbed oxygen, the 3%Zn–Ce0.3 -Al0.4 -Ti catalyst with multi-layered nanosheets structure exhibits excellent NH3 -SCR activity, over 90% NO conversion between 240 °C and 340 °C. In addition, in situ DRIFTS results suggest the SCR reaction mainly follows L-H and E-R mechanisms on 3%-Ce0.3 -Al0.4 -Ti samples, result from the multi-layered nanosheets γ-Al2 O structure improves the BET specific surface area and Ce 3+, promotes the adsorption/activation of more NH3 and NOx species. More interestingly, compared with CeO2 and TiO2 the Zn species prefer to absorbed on nanosheets γ-Al2 O3 with (110) facets, so it can effectively protect CeO2 from poisoning as a sacrificial agent. Graphical abstract: The Ce0.3 -Ti catalyst modified by hierarchical nanosheets γ-Al2 O3 structure showed excellent Zn-posioning resistance in NH3 -SCR reaction, which result from the high BET specific surface area, more Ce 3+ and chemisorbed oxygen, and abundant acid sites. In addition, compared with CeO2 and TiO2 the Zn species prefer to absorbed on nanosheets γ-Al2 O3 with (110) facets, so it can effectively protect CeO2 from poisoning as a sacrificial agent. Image 1 Highlights: Associated to γ-Al2 O3 structure for Zn-poisoning resistance was elucidated. Ce0.3 -Al0.4 -Ti catalyst exhibits excellent Zn-poisoning resistance. More Ce 3+ /Ce 4+ species and acid sites are formed due to the structural effect. γ-Al2 O3 can effectively protect CeO2 from Zn-poisoning as a sacrificial agent.